PWE-160 The Joint Hypermobility Syndrome Is Associated With Functional Dyspepsia And Reflux And Identifies A Subgroup With Somatisation, Chronic Pain And Worse Quality Of Life. (9th June 2014) - Fikree, A; Aktar, R; Farmer, A; Grahame, R; Knowles, C; Aziz, Q
Abstract : Introduction: The Joint hypermobility syndrome (JHS) is a non-inflammatory connective tissue disorder with a prevalence of 20%. It is characterised by joint hypermobility, chronic pain, fibromyalgia (FM) and dysautonomia. Gastrointestinal (GI) symptoms e.g., dyspepsia, reflux, bloating and constipation are present in up to 80% of affected individuals. Small studies suggest that FGID are common in these patients yet no controlled studies have systematically investigated if JHS is associated with particular GI diagnoses nor explored the effect of JHS on non-GI symptom presentation and quality of life (QOL). Methods: Using a nested case-control double-blind study in secondary care GI clinics, consecutive new referrals (without prior GI diagnosis), aged 18–70, completed validated questionnaires for GI, somatic, psychological and autonomic symptoms and QOL, and were assessed for JHS and FM. They then consulted a gastroenterologist, underwent investigations and received a GI diagnosis. ROME III criteria were used to categorise FGID. A control group of patients, aged 18–70, who were referred to secondary care for non-GI related problems, were similarly assessed. The prevalence of JHS in various GI diagnoses and in controls, adjusted for age and gender, was compared. Non-GI characteristics and QOL was compared in JHS and non-JHS patients. Results: 688 GI patients [254 organic: (55% F, 43y); 341 FGID: (65% F, 40y); 53 reflux: (40% F, 46y)] and 93 non-GI controls (67% F, 43y) were included. JHS prevalence was higher in FGID (38%) and reflux (40%) compared to organic disorders (26%) and controls (26%) (p = 0.003). JHS was significantly associated with FGID (ORadj: 1.7, CI:1.02–2.88), specifically postprandial distress syndrome (ORadj 2.2, CI: 1.2–2.2), and with reflux disorders (ORadj 2.2, CI: 1.1–4.7), but not with organic disorders (ORadj: 1.0, CI:0.6–1.8). FGID patients with JHS had significantly more FM (12.6 vs. 4.9%, p = 0.02), chronic pain (23.2 vs. 11.7%, p = 0.01), somatisation scores (13 vs. 10, p < 0.01), anxiety scores (0.5 vs. 0.36, p = 0.02) and urinary autonomic symptoms (30.5% vs 19.6%, p = 0.047), and worse pain related QOL scores (45 vs. 63.5, p < 0.01). Conclusion: JHS is associated with functional dyspepsia, and non-erosive reflux disease, and with FM, chronic pain, somatisation and anxiety. Clinical assessment for JHS in GI clinics is indicated in those with a combination of functional upper GI symptoms and extra-intestinal symptoms as this may help earlier identification of a more 'challenging' group of patients with multiple somatic symptoms and worse QOL. These may benefit from early multidisciplinary approach involving rheumatologists and pain specialists. Disclosure of Interest: None Declared.